Workshop Literasi Numerasi Guru Dengan Strategi Jurnal Entri Ganda Di SMP Negeri 22 Bandar Lampung - Rahayu, Chika; Zakiya, Hanifah; Falamy, Ryna Aulia; Ubaidillah, Muhammad (Pakis Journal Institute, 2024)
Teachers' literacy and numeracy competencies are essential to improve the quality of education and prepare students to face challenges in the modern era and be better prepared to face global challenges. The purpose of this activity is to improve teachers' insights, competencies and understanding of the importance of integrating numeracy literacy in every stage of learning. This workshop was held for two days on October 18-19, 2024, attended by 53 subject teachers who teach at each level in SMP Negeri 22 Bandar Lampung. At the initial stage, a common perception of numeracy literacy was shared and then followed by a more specific strategy through double-entry journals was chosen as a way to improve teachers' competence in making evaluations and learning designs that integrate literacy and numeracy. The workshop was proven to improve teachers' understanding and competence on numeracy literacy from 71.51% to 86.94%. This shows that the workshop can improve teachers' understanding, insight and competence on literacy and numeracy in learning.